Digital analysis of the placement of the tibial tuberosity - Bhat, Rashmi; Rathan, Ramya; Samapriya, Neha; Pai, Shakuntala (International Journal of Research in Medical Sciences, 2016)
Background:The tibial tubersosity is a roughened prominence that serves as the attachment site for the ligamentum patellae and typically varies in size and shape. The objective was to determine the vertical and horizontal position of the tibial tuberosity (TT) and determine the side and the gender differences in 170 adult dry tibias. Methods: 170 randomly collected tibiae of unknown sex were analysed to evaluate the position and the gender differences in the tibia. Horizontal position was assessed using 2 digital photographs of the upper end of the tibia, one being end on view and the other frontal view. The picture thus taken was transferred to the computer and analysed using adobe photoshop version 5.0 software. Results: There was a significant difference (p value = 0.013) in the horizontal position of TT in end on view. The horizontal position of TT (frontal view) was more laterally placed on the right side than the left which was statistically significant (p value= 0.017, nonparametric test). The horizontal position of TT (end on view) was more laterally placed on the left side than right which was not statistically significant. There was no difference in the vertical position of TT. Conclusion: From the results, it can be inferred that, the TT is placed more laterally and occupies approximately 6% of the total length of the tibia in all 170 bones.